The critic of Romani music - Lavička, Vojtěch (Romano džaniben, 2022)
A critical essay in which the author reflects on the development of Romani music from the 1950s to the present, drawing on his professional and personal experiences as a violinist, member of a Romani music group, moderator and publicist.
Keywords: Romani music; Romani music bands